Desarrollo del pensamiento matemático en el aprendizaje de técnicas de conteo (2022)
Eng: The objective of this proposal is to develop mathematical thinking in the learning of some counting techniques. The research has a qualitative approach, under the action-research design with the use of instruments such as participatory observation, open-ended questionnaire and the application of a system of activities to communities of practice conformed by seventh graders. The results show that when the teacher confronts a group of students with the construction of their own concept in mathematics based on problems, they respond effectively, reflecting on the experience accumulated in failed and successful attempts. This shows that mathematical reasoning can be improved with practice and reflection, allowing teachers to take advantage of environments in which questions, contradictions, tensions and surprises enrich their practice and become essential elements that change the way of seeing and feeling mathematics in their students.